2014
DOI: 10.4137/ehi.s15263
|View full text |Cite
|
Sign up to set email alerts
|

Potential Contribution of Work-Related Psychosocial Stress to the Development of Cardiovascular Disease and Type II Diabetes: A Brief Review

Abstract: Two of the major causes of death worldwide are cardiovascular disease and Type II diabetes. Although death due to these diseases is assessed separately, the physiological process that is attributed to the development of cardiovascular disease can be linked to the development of Type II diabetes and the impact that this disease has on the cardiovascular system. Physiological, genetic, and personal factors contribute to the development of both these disorders. It has also been hypothesized that work-related stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…Men and women at the same occupational level have similar response to stress during working hours; whereas after work, men tend to relieve more rapidly than women . It is likely that stress related to home and family life, such as household responsibilities and child care, prolongs reaction to stress in women . This study is the first to test the effect of household burden in the association between work stress and T2DM.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Men and women at the same occupational level have similar response to stress during working hours; whereas after work, men tend to relieve more rapidly than women . It is likely that stress related to home and family life, such as household responsibilities and child care, prolongs reaction to stress in women . This study is the first to test the effect of household burden in the association between work stress and T2DM.…”
Section: Discussionmentioning
confidence: 89%
“…Other factors outside of work, such as stress related to home and family life may pose additional weight to work stress. Some studies reported that combined stress from work and family multiplies the risk of depressive symptoms and accelerates coronary disease progression , indicating that effect of work stress may be amplified by household burden.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a recent study performed among Japanese firefighters, the quantity of work, the role conflict and ambiguity, inadequate support from the supervisor, shift work and low self-esteem were significantly related to depressive symptoms [4]. Occupational stress has also been associated with other physical and behavioral problems such as hypertension [16], cardiovascular disease [17], and alcohol and substance abuse [18]. It is also well documented that employee stress may negatively affect business performance since it has been associated with reduced productivity in the workplace [19].…”
Section: Data Collectionmentioning
confidence: 99%
“…Rodzaje działań profilaktycznych organizowanych przez pracodawcę, którymi są zainteresowani pracownicy wieloprofilowego przedsiębiorstwa Jednym z głównych czynników ryzyka ChUK, postrzeganym jako najczęściej występujący czynnik ryzyka tych chorób w środowisku pracy, jest stres. Wiele badań wskazuje na to, że stres związany z pracą zawodową może bezpośrednio przyczyniać się do rozwoju chorób sercowo-naczyniowych poprzez indukowanie wzrostu ciśnienia tętniczego i zmiany w częstości skurczów serca u pracowników [11][12][13].…”
Section: Omówienieunclassified